Contribution of Contextual Learning Models to Increasing Elementary School Students' Interest in Learning - Lilis Nurhasanah; E. Hasanah; Muh. Hasan Marwiji (Penerbit Presisi Pustaka, 2025)
Learning interest is a critical factor in elementary education, yet it remains low in many classrooms due to conventional teaching methods. This study investigates the implementation of the Contextual Teaching and Learning (CTL) model to enhance the learning interest of lower-grade students at SD Negeri Kuta Cisaat Sukabumi. Using a qualitative case study approach, data were collected through in-depth interviews with three class teachers, participatory classroom observations, and document analysis of lesson plans and student work. The findings indicate that teachers have begun implementing CTL through strategies like simulations and the use of concrete media, which has successfully increased student interest, evidenced by heightened enthusiasm, attention, and curiosity. However, the implementation faces multidimensional constraints, including limited teacher conceptual understanding, insufficient training, lack of teaching resources, and the absence of systematic school policy support. The study concludes that optimizing CTL requires a holistic, systemic approach. Sustainable improvement in student interest depends not only on developing individual teacher competencies but also on building a supportive school ecosystem with clear policies, adequate resource allocation, and a collaborative culture that fosters pedagogical innovation.